2017
DOI: 10.1080/1350293x.2016.1266226
|View full text |Cite
|
Sign up to set email alerts
|

Read-alouds in kindergarten classrooms: a moment-by-moment approach to analyzing teacher–child interactions

Abstract: The aim of the study was to explore teacher-child interaction in 24 whole-class read-aloud sessions in Chilean kindergarten classrooms serving children from low socioeconomic backgrounds. Fifteen sessions focused on story meaning, and nine focused on language coding/decoding. We coded teacher and child turns for their function (i.e., teacher initiation, child response, teacher follow-up), type (e.g., open/closed questions, directives; confirmation, elaboration), and complexity (i.e., literal/low vs. inferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
2
18
0
12
Order By: Relevance
“…An analysis of teacher questioning during book‐reading activities found that the extent to which teachers scaffolded students’ language skills by moving between inferential and literal questions in response to the level of the students’ replies positively related to students’ vocabulary (Mascareño, Deunk, Snow, & Bosker, in press), evidence of effective book discussion practices not typical in Chile. At the same time, the Un Buen Comienzo (A Good Start) professional development program showed a negative impact on the amount of conceptual information provided.…”
Section: The Current Studymentioning
confidence: 99%
“…An analysis of teacher questioning during book‐reading activities found that the extent to which teachers scaffolded students’ language skills by moving between inferential and literal questions in response to the level of the students’ replies positively related to students’ vocabulary (Mascareño, Deunk, Snow, & Bosker, in press), evidence of effective book discussion practices not typical in Chile. At the same time, the Un Buen Comienzo (A Good Start) professional development program showed a negative impact on the amount of conceptual information provided.…”
Section: The Current Studymentioning
confidence: 99%
“…Los investigadores que estudiaron las interacciones PRS entre maestras y niños/as que asisten al preescolar postularon, en general, que dichas interacciones deben ser cognitivamente desafiantes, ayudar al aprendizaje y ser el andamiaje para la construcción del conocimiento (Carlsen, 1991;Chafy & Elkhouzai, 2014;Wang & Wang, 2013). Esto implica que es importante tanto el análisis de la pregunta, caracterizada según su complejidad y tipo, como el análisis del seguimiento, caracterizado según su bajo o alto nivel cognitivo (Mascareño et al, 2017).…”
Section: Interacciones Pregunta-respuesta-seguimiento (Prs)unclassified
“…La complejidad de la pregunta se refiere a la distinción entre preguntas literales, cuya respuesta está disponible a través de la percepción o la memoria, y preguntas inferenciales, en las cuales la información no está disponible en el contexto inmediato o no ha sido previamente proporcionada (Mascareño et al, 2017;Sembiante et al, 2018;van Kleeck et al, 2006). Las preguntas inferenciales requieren información externa relevante para la elaboración de inferencias o conclusiones, por lo que propician discusiones con lenguaje abstracto y explicaciones de causa-efecto (Sembiante et al, 2018;van Kleeck et al, 2006).…”
Section: Interacciones Pregunta-respuesta-seguimiento (Prs)unclassified
See 1 more Smart Citation
“…-Apprendre à comprendre, ensemble, un texte, en profondeur Plusieurs auteurs (Blewitt, Rump, Shealy et al, 2009 ;Cabell, Justice, McGinty et al, 2015 ;Wasik & Hindman, 2011) ont montré que les enseignants qui font discuter le sens des histoires aident leurs élèves à mieux les comprendre et à mieux les interpréter, mais à deux conditions : 1 o qu'ils les sollicitent dans de multiples registres cognitifs : reformulation, description, explication, résumé, discussion, argumentation, mise en lien avec l'expérience personnelle… (Dickinson & Smith, 1994) ; 2 o qu'ils leur fassent réaliser des activités présentant de véritables défis cognitifs (Massey, 2004 ;Mascareño, Deunk, Snow et al, 2017). C'est pourquoi Narramus propose une approche intégrative de l'enseignement de la compréhension et de la narration en prenant appui sur des albums.…”
Section: Les Caractéristiques Des Pratiques D'enseignement Efficacesunclassified